2017
DOI: 10.1158/1538-7445.am2017-5133
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 5133: TP-1287, an oral prodrug of the cyclin-dependent kinase-9 inhibitor alvocidib

Abstract: Alvocidib is a potent inhibitor of cyclin-dependent kinase-9 (CDK9) and induces apoptosis in cancer cells by reducing the expression of short-lived, anti-apoptotic proteins such as MCL-1. Alvocidib, as a part of a sequential combination regimen with cytarabine and mitoxantrone (ACM), is currently in a Phase II clinical trial in relapsed/refractory acute myeloid leukemia (AML). Patients with AML that have a high dependence on MCL-1 are considered more likely to benefit from the alvocidib-containing regimen. MCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…There is an open clinical question as to whether transcriptional inhibitors can exploit this vulnerability with acceptable toxicity profiles. Currently, several transcriptional CDK inhibitors, including CDK9-preferring inhibitors, are either in clinical trials or in late-stage preclinical development (Bisi et al, 2017;Cidado et al, 2020;Clark et al, 2017;Goh et al, 2012;Hu et al, 2019;Kawakami et al, 2019;Kim et al, 2017;L€ ucking et al, 2017). Many of these drugs have activity against multiple CDKs, making it difficult to fully assess the specific contribution of CDK9 inhibition to efficacy.…”
Section: Article Discussionmentioning
confidence: 99%
“…There is an open clinical question as to whether transcriptional inhibitors can exploit this vulnerability with acceptable toxicity profiles. Currently, several transcriptional CDK inhibitors, including CDK9-preferring inhibitors, are either in clinical trials or in late-stage preclinical development (Bisi et al, 2017;Cidado et al, 2020;Clark et al, 2017;Goh et al, 2012;Hu et al, 2019;Kawakami et al, 2019;Kim et al, 2017;L€ ucking et al, 2017). Many of these drugs have activity against multiple CDKs, making it difficult to fully assess the specific contribution of CDK9 inhibition to efficacy.…”
Section: Article Discussionmentioning
confidence: 99%
“…This phosphate prodrug has an improved solubility under neutral or basic conditions allowing oral administration of the drug. Pharmacodynamic and efficacy studies in acute myeloid leukemia ( Kim et al., 2017 ) and prostate cancer ( Forostyan et al., 2019 ) xenografted models, showed that orally delivered TP-1287 is efficiently metabolized and enhances tumor regression in vivo . A phase I study using oral TP-1287 is actively recruiting to determine the maximum tolerated dose (MTD) and dose-limiting toxicities (DLTs) in patients with advanced metastatic or progressive solid tumors who are refractory to established therapy ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…208 TP-1287 has shown in vivo efficacy in the MV-4-11 AML mouse xenograft model with 109% TGI at 7.5 mg/kg, PO. 208 Tolero Pharmaceuticals, Inc., is evaluating TP-1287 in phase I clinical trial in patients with advanced solid tumors. 209 P276-00 (riviciclib, 72) is the second candidate that emerged from this skeleton 210 211 In its phase II clinical trial in 13 patients with relapsed or refractory MCL, two patients had stable disease at the end of the P276-00 treatment, whereas 11 patients experienced treatment-related AE's.…”
Section: Aminopyridinesmentioning
confidence: 98%
“…Currently, it is being investigated in two trials in combination with venetoclax for AML, 206 and in combination with decitabine for MDS 207 . Tolero pharmaceuticals discovered an orally active TP‐1287 ( 71 ), a phosphate prodrug of flavopiridol which gets enzymatically cleaved to its active metabolite flavopiridol at the tumor site 208 . TP‐1287 has shown in vivo efficacy in the MV‐4‐11 AML mouse xenograft model with 109% TGI at 7.5 mg/kg, PO 208 .…”
Section: Cdk Inhibitors In Clinical and Preclinical Pipelinementioning
confidence: 99%
See 1 more Smart Citation